Multi-catheter interstitial brachytherapy for partial breast irradiation: an audit of implant quality based on dosimetric evaluation comparing intra-operative versus post-operative placement - Lavanya Gurram; Tabassum Wadasadawala; Kishor Joshi; Reena Phurailatpam; Siji Paul; Rajiv Sarin (Journal of Contemporary Brachytherapy, 2016)
Purpose : The use of multicatheter interstitial brachytherapy (MIB) for accelerated partial breast irradiation (APBI) in early breast cancer (EBC) patients outside the trial setting has increased. Hence, there is a need to critically evaluate implant quality. Moreover, there is a scarcity of reports using an open cavity technique. We report the dosimetric indices of open and closed cavity MIB techniques. Material and methods: The dosimetric parameters of 60 EBC patients treated with MIB (open and closed cavity) who underwent three dimensional, computerized tomography (CT) based planning for APBI from November 2011 to July 2015 were evaluated. Coverage Index (CI), Dose Homogeneity Index (DHI), Conformity Index (COIN), Plan Quality Index (PQI), and Dose Non-uniformity Index (DNR) were assessed. Results : Forty-one patients underwent open cavity and 19 patients underwent closed cavity placement of brachytherapy catheters. The median number of planes was 4 and median number of needles was 20. Median dose was 34 Gy with dose per fraction of 3.4 Gy, given twice a day, 6 hours apart. The D90 of the cavity and clinical target volume (CTV) were 105% and 89%, respectively. The median doses to the surgical clips were greater than 100%. The median CI of the cavity and CTV was 0.96 and 0.82, respectively. The DHI and COIN index of the CTV was 0.73 and 0.67. There were no significant differences in the dosimetric parameters based on whether the technique was done open or closed. Conclusions : Critical evaluation of the dosimetric parameters of MIB-APBI is important for optimal results. While the open and closed techniques have similar dosimetry, our institutional preference is for an open technique which eases the procedure due to direct visualization of the tumor cavity.